2005
DOI: 10.1359/jbmr.041127
|View full text |Cite
|
Sign up to set email alerts
|

Initial Years of Recreational Artistic Gymnastics Training Improves Lumbar Spine Bone Mineral Accrual in 4- to 8-Year-Old Females

Abstract: Gymnasts' bone mineral characteristics are generally not known before starting their sport. Prepubertal females who enrolled in beginning artistic gymnastics (n = 65) had lower bone mineral than controls (n = 78). However, 2 years of gymnastics participation versus no participation led to a significantly greater accrual of forearm bone area and lumbar spine areal BMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
52
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 53 publications
7
52
0
5
Order By: Relevance
“…These findings parallel previous observation in children involved in recreational gymnastics [11,14]. Laing and colleagues [31] found that 4-8-year-old girls participating in 1 h of recreational gymnastics per week gained larger bone area at the forearm over 2 years compared to girls participating in non-gymnastic activities as estimated by DXA. Erlandson et al [11] have previously reported in this cohort that individuals involved in recreational gymnastics had 3 % greater total body BMC and 7 % more FN BMC.…”
Section: Discussionsupporting
confidence: 85%
“…These findings parallel previous observation in children involved in recreational gymnastics [11,14]. Laing and colleagues [31] found that 4-8-year-old girls participating in 1 h of recreational gymnastics per week gained larger bone area at the forearm over 2 years compared to girls participating in non-gymnastic activities as estimated by DXA. Erlandson et al [11] have previously reported in this cohort that individuals involved in recreational gymnastics had 3 % greater total body BMC and 7 % more FN BMC.…”
Section: Discussionsupporting
confidence: 85%
“…Previous researchers, however, have found that young competitive gymnasts not only have greater aBMD as assessed by cross-sectional comparison but also accrue more bone over time, suggesting that gymnastics training during growth is at least partially responsible for the greater BMC and aBMD observed in young gymnasts. (19,45,46) Nonetheless, the potential role of genetics and self selection into the sport should also be considered whenever assessing the impact of gymnastics training on bone parameters. Physical activity and diet were assessed using self-report questionnaires.…”
Section: Discussionmentioning
confidence: 99%
“…physically active pre-pubertal children appear to develop bone of greater size than their sedentary peers, although this effect is confined to the loaded regions. [59,62] Although well documented reviews have been published in postmenopausal women, [3,40,42,63] less is known about the effects that exercise programmes and sports participation may have on bone mass in young adult women at premenopausal age. [64] Thus, this article focuses on the influence of physical activity on BMC and BMD in premenopausal and postmenopausal women and in men.…”
Section: Exercise and Bone Mass In Adults 441mentioning
confidence: 99%